Public Health History Corner - The far-sighted: Alessandro Seppilli (Italian Journal of Public Health, 2011)
Alessandro Seppilli is one of the main protagonists for the planning and establishment of the Italian National Health Service [1]. As Chairman of the Commission for the study of health reform in the Italian Consiglio Superiore di Sanità (Higher Council of Health). As a lecturer and researcher he promoted and led several important lines of research, always ahead of its time and with great foresight. His curiosity led him to be involved in a variety of Public Health disciplines: water and sanitation, safe milk distribution, as well as demonstrating, through research, the influence of atmospheric electrical changes on biological phenomena in respect to the vital effects of electric fields changes. He also conducted pioneering research into the study of anticaries fluoride and the carcinogenic effects of active and passive cigarette smoke. Last but not least he studied the use of low temperatures for food storage, investigated the distribution of drinking water by alternative systems and undertook studies on environmental carcinogenesis.